Reguladores do metabolismo bacteriano em reservatórios tropicais - Silva, Roberta Mafra Freitas da (Universidade Federal de São Carlos, 2017)
Reservoirs located in tropical regions are main carbon (C) sources to the atmosphere, and bacterial metabolism is a key process that regulates those emissions. However, studies on the environmental drivers of bacterial metabolism in tropical reservoirs are scarce. By measuring metabolic rates and the limnological parameters in four cascading reservoirs that form a trophic state gradient, we determined the environmental drivers of bacterial metabolism in a tropical region, and compared them with those found in the literature (mainly from temperate regions). Our multiple regression models selected variables related to the trophic state as the main drivers of bacterial production (BP) and bacterial growth efficiency (BGE). On the other hand, bacterial respiration (BR), and consequently bacterial carbon demand (BCD), were weakly and negatively correlated to dissolved organic carbon (DOC), contrasting with the literature data. BR was always high, especially in less productive reservoirs where planktonic communities were limited by phosphorus. Nutrient limitation, high temperatures and high incident light intensity increased the environmental hostility, and cells must invest more energy in maintenance mechanisms, which directs the metabolism towards BR. This was observed in the reservoirs studied, especially in the more oligotrophic environments (Nova Avanhandava and Três Irmãos) where BR was higher and ECB lower. Our results indicate that the regulatory mechanisms of bacterial metabolism may vary according to latitude.
Environmental drivers of bacterial metabolism in tropical reservoirs
Keywords: Produção bacteriana; Respiração bacteriana; Eficiência de crescimento bacteriano; Demanda de carbono bacteriano; Gradiente de produtividade; Bacterial production; Bacterial respiration; Bacterial growth efficiency; Bacterial carbon demand; Productivity gradient; CIENCIAS BIOLOGICAS::ECOLOGIA